2011
DOI: 10.3109/0142159x.2011.587915
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of learner outcomes in interprofessional continuing education: A literature review and an analysis of survey instruments

Abstract: No gold-standard tool has been agreed upon in the literature, and none fully addresses all IPE learner outcomes. Objective measures of higher level outcomes are necessary to ensure comprehensive evaluation of IPE/IPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 46 publications
2
47
0
2
Order By: Relevance
“…In summary, the findings of the review suggest that pre-licensure and post-licensure learners react favorably to the use of ICTs in the delivery of IPE, and ICT-mediated IPE can lead to positive attitudinal and knowledge change consistent with what has been reported with traditional methods of IPE delivery (Gillian, Lovrics, Halpern, Wiljer, & Harnett, 2011;Reeves et al, 2010). Findings at behavioral, organizational, and patient outcome levels of evaluation, while suggestive of positive trends, were not supported by overly robust, rigorous, and reliable study designs and measurements.…”
Section: Concluding Commentssupporting
confidence: 56%
“…In summary, the findings of the review suggest that pre-licensure and post-licensure learners react favorably to the use of ICTs in the delivery of IPE, and ICT-mediated IPE can lead to positive attitudinal and knowledge change consistent with what has been reported with traditional methods of IPE delivery (Gillian, Lovrics, Halpern, Wiljer, & Harnett, 2011;Reeves et al, 2010). Findings at behavioral, organizational, and patient outcome levels of evaluation, while suggestive of positive trends, were not supported by overly robust, rigorous, and reliable study designs and measurements.…”
Section: Concluding Commentssupporting
confidence: 56%
“…The lack of outcome focused research is in keeping with many reviews of educational interventions [19][20][21] . However, the difficulty in undertaking this research should not prevent it from happening.…”
Section: Discussionmentioning
confidence: 99%
“…23 Using the Kirkpatrick/Barr hierarchy of learner outcomes 24 they were unable to find a single instrument to comprehensively assess all IPE learner outcomes. They found that few instruments directly measured higher levels of learning, such as changes in behaviour, effect on the organisation and impact on patient outcomes, but often relied on the learner's perspective of the impact.…”
Section: Challenges Of Evaluating Ipementioning
confidence: 99%